Single-phase grounding fault line selection method of ring neutral point-ungrounded power distribution network - YE ZHIYUN; DUAN ZHUCHAO; TANG YI; CHEN KUI; LIU HAO; LIU XUECHAO; FANG YONGLI (2017)
The invention discloses a single-phase grounding fault line selection method of a ring neutral point-ungrounded power distribution network. According to the method of the invention, whether a single-phase grounding fault occurs is judged through detecting the zero-sequence voltage of the ring neutral point-ungrounded power distribution network; when the single-phase grounding fault occurs, the zero sequence current of each loop line and feeder line is detected; and whether a loop line malfunctions or a feeder line malfunctions can be distinguished according to the characteristics of the vector sum of the zero sequence current at two ends of each of all loop lines, if a loop line fault malfunctions, the malfunctioned loop line be judged through comparing the characteristics of the zero sequence vector sum of two sides of each of the loop lines, if a feeder line malfunctions, the malfunctioned feeder line be judged through comparing the directions of the zero sequence current of all feeder lines in each substat